Most admired training transfer enterprise model in - Raja Suzana Raja Kasim; Adnan Omar; Sharrifah Ali; Zulazli Hashim (Elsevier, 2013)

(untitled)
The recognition of training as an important development of human resource in implementing the quality of its human